Peculiarities of real-world data application for health technology assessment in Asian countries - B. B. Kondratyeva; F. V. Gorkavenko; V. V. Omelyanovskiy (IRBIS LLC, 2024)
The article is devoted to the study of regulatory approaches to the sphere of real-world data (RWD) and real world evidence (RWE) in the countries of the Asia-Pacific Region (China, South Korea, Japan, Taiwan, etc.) and examples of their practical application for health technology assessment. The peculiarities of collecting and gaining access to RWD/RWE in Asian countries, prerequisites for the development of this direction, adopted regulations, developed methodological guidelines, promising areas of application, and clinical and economic research based on country-specific data are considered. The existing practices in Asian countries represent valuable experience, some of which could be considered for implementation in the national practice.